PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS HOTS (KETERAMPILAN BERPIKIR TINGKAT TINGGI) PADA TEMA EKOSISTEM SISWA KELAS V SD - I Gede Wisnu Antara; Ida Bagus Putu Arnyana; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the validity and reliability of the development of the instrument of higher order thinking skills (HOTS) of Science in class V SD in Cluster VI, Penebel District. This type of research is research and development or research and development with 4D stages, consisting of 4 stages, namely define, design, develop and desimination. However, the desimination stage was not carried out due to the public health situation with the Covid 19 pandemic. At this stage it produced an instrument of higher order thinking skills in the form of multiple choices, which was then validated by a team of experts which was then tested on students. Based on the results of expert validation on the material, construction, and language aspects, the instrument was declared valid in the very good category. The validity of the test content through expert testing using CVR analysis obtained valid results for all questions. The results of the validity of the items with the point biserial formula obtained that all items had rcount> rtable so that all items were declared valid. The reliability test results obtained a value of 0.91 in the range 0.80 <r1.1 <1.00 or in the category of very high degrees of reliability. So the instrument for assessing higher order thinking skills (HOTS) that has been developed has been valid and reliable to be used in measuring students' higher order thinking skills.